Análise do perfil dos empreendedores e empreendimentos da cidade de Tibau do Norte - RN - Fonseca, Ana Karolina Frutuoso (Universidade Federal Rural do Semi-Árido, 2020)
When observing the increase of the enterprises in the last years in Brazil, the referred work had as main objective to characterize and to analyze the enterprises and profile of the entrepreneurs of the commercial center of Tibau do Norte-RN. The work methodology was carried out with research techniques and data collections. For data collection, a questionnaire was used as an aid, which was prepared by prof. Dr. Maristélio da Cruz Costa for his project on entrepreneurship in the State of Rio Grande do Norte. The survey was conducted in the city of Tibau do Norte-RN, where 14 entrepreneurs were interviewed. In addition, the descriptive statistics performed by the GEM was used as a basis for data analysis. Through data analysis, it was noted that the majority of entrepreneurs working in the municipality are female, have completed high school and are aged between 31 and 40 years. Based on the study, it is clear that women are increasingly gaining space in the job market.
Monografia
Keywords: Empreendedorismo; Empreendimentos; Empreendedores; Tibau do Norte; Entrepreneurship; Enterprises; Entrepreneurs; Tibau do Norte; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA